Atypical subacute sclerosing panencephalitis presenting in a toddler with a short latency period: Evolving epidemiological trend (Indian Journal of Case Reports, 2020)
Subacute sclerosing panencephalitis (SSPE) is a slowly progressive degeneration of the central nervous system (CNS) caused by a persistent defective measles virus infection. We report the case of a 2.5-year-old girl who presented with complaints of sudden onset frequent falls while walking, myoclonic jerks, and loss of speech. The electroencephalogram showed generalized slowing with irregular activity and cerebral magnetic imaging revealed T2 hyperintensities in the periventricular region in the parietal and occipital lobes. SSPE was considered and the diagnosis was confirmed with the identification of measles antibodies in cerebrospinal fluid. Our findings show that SSPE should be in mind in the differential diagnosis of meningoencephalitis even when a short latency period with measles infection.